Moving toward authentic, learning-oriented assessment in coach education - McCarthy, L.; Allanson, A.; Stoszkowski, J. (International Sport Coaching Journal, 2021)
As sports coaching continues to professionalize, the demand for and importance placed upon high-quality education and development programs for sports coaches is increasing. As a result, the landscape of provision is changing, and there is now a recognition of the key role that higher education institutes play in the education, development, and assessment of sports coaches. In this insights article, the authors argue that as there is a scarcity of research focused solely on assessment as a feature of coach education programs, there is something to be gained from examining how higher education institutes assess sports coaches. This represents an important contribution to the research literature, given that assessment is a feature of nearly all coach education programs and that the attainment of a specific award communicates to stakeholders (e.g., employers, athletes, parents) that a precise standard of practice has been met. As such, the authors identify how some higher education institutes are addressing the issue of assessment with sports coaches and highlight a series of assessment principles, alongside practical examples from the literature, which are intended to stimulate conversation in what the authors argue is an important area of study.